Effects of gelsemine on oxidative stress and DNA damage responses of Tetrahymena thermophila - Ye, Qiao; Feng, Yongyong; Wang, Zhenlu; Jiang, Wenzhao; Qu, Yuexin; Zhang, Chaonan; Zhou, Aiguo; Xie, Shaolin; Zou, Jixing (PeerJ, 2018)
Gelsemine is an important toxic substance extracted from Gelsemium elegans, which has a lot of biological functions in cells and organisms, but its toxicity has been rarely reported in Tetrahymena thermophila. In this study, we used the protozoan T. thermophila as an experimental model to investigate the potential toxicity-induced mechanism of gelsemine in the unicellular eukaryote. Our results clearly showed gelsemine inhibited T. thermophila growth in a dose-dependent manner. This exposure also resulted in oxidative stress on T. thermophila cells and antioxidant enzyme levels were significantly altered at high gelsemine levels (p < 0.05). Gelsemine produced a slight apoptotic effect at the highest (0.8 mg/mL) gelsemine level used here (p < 0.05). Furthermore, the toxin-induced DNA damage in a dose-dependent manner. The ultrastructural analysis also revealed mitophagic vacuoles at 0.4 and 0.8 mg/mL levels of gelsemine exposure. Moreover, expressions of oxidative stress-related and MAP kinase genes were significantly changed after exposure to 0.8 mg/mL level of gelsemine (p < 0.05). Altogether, our results clearly show that gelsemine from G. elegans can inhibit the growth via inducing oxidative stress and DNA damage in T. thermophila cells.
Keywords: T. thermophila; Gelsemine; Gene expression; Oxidative stress; DNA damage